Dose Optimization of 17 α-Methyltestosterone to Maximize Sex Reversal of Nile Tilapia (Oreochromis Niloticus) (Research in Agriculture Livestock and Fisheries, 2023)
The study investigated the optimum dose of 17 α-methyltestosterone (17α–MT) for maximum sex reversal and growth performance of Nile tilapia (Oreochromis niloticus). Using a completely randomized design, three treatments (Control, T-1, T-2, and T-3) in triplicates were set up. The control group diet was devoid of 17α–MT. The remaining three groups, T-1, T-2, and T-3, were fed feed that contained 30, 60, and 100 mg kg-1 of 17α–MT, respectively. Fry of three days old were stocked at a rate of 100 per tank. They were fed with experimental diet for 28 days. After the hormone treatment and 90 days of rearing the highest survival rate was found in the control group. Gonadal squashing of O. niloticus showed different sex ratios for different treatments. The control group showed a normal sex ratio of 48.33% males and 51.67% females. The experimental group T-3 showed the highest percentage of males (98.33%) followed by T-2 (93.33%) and T-1 (76.66%). After 90 days of rearing, although the study found the highest mean length (82.12±1.5 mm), weight (26.74±0.08 g) and SGR (9.17±0.05%) in the treatment T2, these growth performance parameters did not differ significantly with the result of treatment T3. The Nile tilapia's sex ratio has been found to be more affected by a higher dose, or 100 mg 17α–MT kg-1 of feed. With the increase of hormone inclusion level, sex reversal percentage increases. Higher doses of 17α–MT have also a positive impact on Nile tilapia growth performance. Growth increases with the increasing 17α–MT level up to 60 mg in the diet of O. niloticus. Based on the study, the recommended dose for producing maximum mono-sex male tilapia in commercial hatcheries may be 100 mg 17α–MT kg-1 feed.Vol. 9, No. 3, December 2022: 377-384